Acceptance and commitment therapy for adults with advanced cancer (CanACT): study protocol for a feasibility randomised controlled trial. Issue 1 (December 2016) - Low, Joseph; Serfaty, Marc; Davis, Sarah; Vickerstaff, Victoria; Gola, Anna; Omar, Rumana; King, Michael; Tookman, Adrian; Austen, Janet; Turner, Karen; Jones, Louise
Abstract Background One-third of people with cancer experience psychological distress and may suppress distressing thoughts, emotions, and concerns, leading to further problems. Conventional psychological treatments reduce distress by problem solving, but in advanced cancer, when ill health is progressive and death may be approaching, physical and psychological difficulties are complex and have no simple solutions. Acceptance and Commitment Therapy encourages acknowledgement and acceptance of mental experiences, increasing people's ability to work with problems that cannot be solved. Previous pilot work in advanced cancer confirms that distress can be associated with an avoidance of experiencing uncomfortable thoughts and emotions. Methods/Design This feasibility randomised controlled trial of Acceptance Commitment Therapy aims to establish parameters for a larger trial. Fifty-four participants with advanced cancer will be randomly allocated to up to eight sessions (each 1 hour) of Acceptance Commitment Therapy or a talking control. Participants will be recruited from those attending outpatient services and hospice day care at three specialist palliative care units in North and East London, United Kingdom. The primary outcome is a measure of functioning in four areas of life (physical, social/family, emotional, and general activity) using the Functional Assessment of Cancer Therapies - General questionnaire at 3 months after randomisation. Secondary outcomes are (i) acceptance using the Acceptance and Action Questionnaire; (ii) psychological distress using the Kessler Psychological Distress Scale; (iii) physical functioning using a timed walk and sit-to-stand test; and (iv) quality of life measures including the Euroqol-5 Dimensions and ICECAP Supportive Care measures. Qualitative data will be collected at 3 months to explore the participants' experiences of the trial and therapy. Data will be collected on the costs of care. Discussion Data generated on the recruitment, retention, and experience of the interventions and the usefulness of the outcome measures will inform the adaptations required and whether changes in function are consistent with existing data when planning for a sufficiently powered randomised controlled trial. Trial registration ISRCTN13841211 (registered 22 July 2015).